1999
DOI: 10.1034/j.1399-3054.1999.106111.x
|View full text |Cite
|
Sign up to set email alerts
|

Root-applied cytokinin reduces lead uptake and affects its distribution in Norway spruce seedlings

Abstract: sulphur and phosphorus. As a result of reduced uptake, nega-Hydroponically grown Picea abies (L.) Karst. seedlings were exposed to lead (5 mM Pb) and zeatin-riboside (ZR) treat-tive effects of Pb on root elongation were largely ameliorated by ZR. In addition, ZR alleviated the Pb-induced decrease in ments (1 mM, periodically) in a factorial experiment. Exposure of the roots to cytokinin reduced the total Pb content in photosynthetic pigments, although it stimulated Pb translocathe spruce seedlings by ca. 50%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…The situation becomes even more complex considering that translocation to the shoot may also be affected by the hormonal status of the plant. Vodnik et al (1999) showed that increased Pb tolerance of Picea abies seedlings induced by external supply of cytokinins to the roots was associated with decreased root but increased shoot contents of Pb. Although the mechanism(s) underlying phytohormone effects on metal distribution within the plant are not understood at present ( Vodnik et al 1999), the results clearly demonstrate that metal translocation to the shoot is not a simple, uncontrolled process in which a fixed proportion of metals taken up by the roots is delivered to the shoots.…”
Section: Mechanisms Of Ameliorationmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation becomes even more complex considering that translocation to the shoot may also be affected by the hormonal status of the plant. Vodnik et al (1999) showed that increased Pb tolerance of Picea abies seedlings induced by external supply of cytokinins to the roots was associated with decreased root but increased shoot contents of Pb. Although the mechanism(s) underlying phytohormone effects on metal distribution within the plant are not understood at present ( Vodnik et al 1999), the results clearly demonstrate that metal translocation to the shoot is not a simple, uncontrolled process in which a fixed proportion of metals taken up by the roots is delivered to the shoots.…”
Section: Mechanisms Of Ameliorationmentioning
confidence: 99%
“…Vodnik et al (1999) showed that increased Pb tolerance of Picea abies seedlings induced by external supply of cytokinins to the roots was associated with decreased root but increased shoot contents of Pb. Although the mechanism(s) underlying phytohormone effects on metal distribution within the plant are not understood at present ( Vodnik et al 1999), the results clearly demonstrate that metal translocation to the shoot is not a simple, uncontrolled process in which a fixed proportion of metals taken up by the roots is delivered to the shoots. As mycorrhizal fungi alter the hormonal status of their hosts ( Gogala 1991), it is likely that these changes in phytohormones may indirectly affect metal concentrations in the shoot in a presently unpredictable manner.…”
Section: Mechanisms Of Ameliorationmentioning
confidence: 99%
“…In addition, chlorophyll (b) appears to be more sensitive than chlorophyll (a) (Wozny et al, 1995;Vodnik et al, 1999). However, these effects vary among plant species.…”
Section: Discussionmentioning
confidence: 99%
“…The major proportion of metals is located in plant rhizodermis and cortex during their uptake by roots (Obroucheva et al 1998;Tung and Temple 1996;Vodnik et al 1999;Seregin and Ivanov 2001). Seregin and Kozhevnikova (2008) have reviewed the role of various tissues of roots and shoots in HM transport and accumulation in the two plant groups (excluders and hyperaccumulators) and classified these tissues on their participation in transfer and distribution of some HM (Cd, Pb, Ni, Sr) in plants as: (i) absorbents (rhizodermis), (ii) with barrier functions (endodermis and exodermis), iii) accumulators and presentators (epidermis and cortex), (iv) collectors (pericycle), v) inter-organic transporters (xylem and phloem), (vi) storage (root apex).…”
Section: Mechanisms Of Uptake and Translocation Of Contaminants In Plmentioning
confidence: 99%